2005
DOI: 10.1038/sj.npp.1300761
|View full text |Cite
|
Sign up to set email alerts
|

Cholinesterase Inhibitors Ameliorate Behavioral Deficits Induced by MK-801 in Mice

Abstract: Enhancing cholinergic function has been suggested as a possible strategy for ameliorating the cognitive deficits of schizophrenia. The purpose of this study was to examine the effects of acetylcholinesterase (AChE) inhibitors in mice treated with the noncompetitive Nmethyl-d-aspartate (NMDA) receptor antagonist, MK-801, which has been suggested as an animal model of the cognitive deficits of schizophrenia. Three separate experiments were conducted to test the effects of physostigmine, donepezil, or galantamine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
45
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(51 citation statements)
references
References 55 publications
5
45
0
1
Order By: Relevance
“…*P < 0.05, **P < 0.01, ***P < 0.001 vs. controls (V); # P < 0.05, ## P < 0.01 vs. scopolamine-treated animals (Sc). excitatory circuit receives tonic excitatory cholinergic input from the medial septum and the diagonal band of Broca and glutamate, acting on NMDA receptors located on inhibitory GABAergic interneurons within the septum, inhibits the activity of cholinergic neurons that project to the hippocampus (11). Consistent with this localization, behavioral and electrophysiological studies have shown that memantine increases cholinergic signaling and excitability in mouse hippocampus and that this action is blocked by the muscarinic antagonist scopolamine (7).…”
mentioning
confidence: 66%
“…*P < 0.05, **P < 0.01, ***P < 0.001 vs. controls (V); # P < 0.05, ## P < 0.01 vs. scopolamine-treated animals (Sc). excitatory circuit receives tonic excitatory cholinergic input from the medial septum and the diagonal band of Broca and glutamate, acting on NMDA receptors located on inhibitory GABAergic interneurons within the septum, inhibits the activity of cholinergic neurons that project to the hippocampus (11). Consistent with this localization, behavioral and electrophysiological studies have shown that memantine increases cholinergic signaling and excitability in mouse hippocampus and that this action is blocked by the muscarinic antagonist scopolamine (7).…”
mentioning
confidence: 66%
“…The lack of benefit of donepezil in the MK801 (PPI) model contrasts with behavioral studies in mice (Csernansky et al, 2005) where donepezil attenuated MK801-induced deficits in fear conditioning as well as spatial and reversal learning better than galantamine. The basis of the differential effects of the compounds observed in our studies and the one cited above is unclear, although there are some differences in the pharmacology of these compounds (i.e., other than that related to AChEI activity) that may be of importance.…”
Section: Discussionmentioning
confidence: 88%
“…The ameliorative effect of BS on the working memory deficit was further supported by the data obtained from the modified version of the Ymaze test. Previous studies demonstrated that central cholinergic and glutamatergic systems are involved in short-term spatial working memory performance elucidated by the modified Y-maze test since the muscarinicreceptor antagonist scopolamine and the anti-NMDAreceptor antagonist MK-801 interfere with the performance in a manner reversible by AChE inhibitors (9,28). In this study, we found that, consistent with previous reports (8 -10), OBX mice exhibited significantly impaired spatial working memory performance in the modified Y-maze test, and that the impairment was reversed by tacrine and BS but not by imipramine.…”
Section: Discussionmentioning
confidence: 99%